The Relationship Between Random Blood Glucose Levels and The Incidence of Diabetic Foot Ulcers - Nur Nunu Prihantini; Fri Rahmawati; Zefeilyne Angelita Permata Sitorus; John Jackson Yang; Frisca Angreni (International Journal of Health and Pharmaceutical (IJHP), 2026)
Diabetes mellitus is a global health challenge characterized by an ever-increasing number of cases annually. The most feared chronic complication of diabetes mellitus is diabetic foot ulcer (DFU), which significantly increases the risk of amputation and mortality rates. This study aims to analyze the relationship between random blood sugar (RBS) levels and the incidence of DFU in type 2 diabetes mellitus patients at Paragon Hospital, Citeureup 2026. The research method used is an analytical observational design with a cross-sectional approach. A total of 54 subjects meet the inclusion criteria out of 109 type 2 diabetes mellitus patients. Medical record data were statistically analyzed using the Chi-Square test. The results indicated that DFU patients were predominantly male (53.7%) and belonged to the 46-55 age group (38.9%). Clinical findings showed that the majority of research subjects (88.9%) had high random blood sugar levels (≥ 200 mg/dL). Statistical test results yielded a p-value of 0.000 (p < 0.05), indicating a significant relationship between high RBS levels and the incidence of DFU. Based on the result the concluded that uncontrolled RBS levels are a primary trigger for DFU. Chronic hyperglycemia triggers vascular and nerve damage, which inhibits the tissue healing process in the feet. Optimal control of RBS levels is essential as a preventive measure to avoid amputation complications in type 2 diabetes patients.